Examining the Effects of Psychological Safety, Transformational Leadership, Job Autonomy, and Employee Creativity on Innovative Work Behavior - I Ketut Damana; Surnadi; Flora Grace Putrianti; Noorhani Dyani Laksmi (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the effects of psychological safety, transformational leadership, job autonomy, and employee creativity on innovative work behavior. A quantitative research design was employed using a cross-sectional survey approach, with data collected from 200 employees across various industries. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. The results indicate that psychological safety, transformational leadership, job autonomy, and employee creativity all have significant positive effects on innovative work behavior. Among these variables, employee creativity was found to be the strongest predictor, highlighting its central role in driving innovation. Additionally, the model demonstrates strong explanatory power, indicating that the integration of psychological, leadership, and job design factors provides a comprehensive understanding of innovative work behavior. The findings suggest that organizations should foster a supportive and safe work environment, promote transformational leadership practices, and provide employees with greater autonomy to enhance creativity and innovation. This study contributes to the literature by offering an integrated framework that explains how multiple organizational factors interact to influence employee innovation.